Complement Modulation of Anti‐Aging Factor Klotho in Ischemia/Reperfusion Injury and Delayed Graft Function. Issue 1 (17th August 2015) - Castellano, G.; Intini, A.; Stasi, A.; Divella, C.; Gigante, M.; Pontrelli, P.; Franzin, R.; Accetturo, M.; Zito, A.; Fiorentino, M.; Montinaro, V.; Lucarelli, G.; et al.
Abstract : Klotho is an anti‐aging factor mainly produced by renal tubular epithelial cells (TEC) with pleiotropic functions. Klotho is down‐regulated in acute kidney injury in native kidney; however, the modulation of Klotho in kidney transplantation has not been investigated. In a swine model of ischemia/reperfusion injury (IRI), we observed a remarkable reduction of renal Klotho by 24 h from IRI. Complement inhibition by C1‐inhibitor preserved Klotho expression in vivo by abrogating nuclear factor kappa B (NF‐kB) signaling. In accordance, complement anaphylotoxin C5a led to a significant down‐regulation of Klotho in TEC in vitro that was NF‐kB mediated. Analysis of Klotho in kidneys from cadaveric donors demonstrated a significant expression of Klotho in pre‐implantation biopsies; however, patients affected by delayed graft function (DGF) showed a profound down‐regulation of Klotho compared with patients with early graft function. Quantification of serum Klotho after 2 years from transplantation demonstrated significant lower levels in DGF patients. Our data demonstrated that complement might be pivotal in the down‐regulation of Klotho in IRI leading to a permanent deficiency after years from transplantation. Considering the anti‐senescence and anti‐fibrotic effects of Klotho at renal levels, we hypothesize that this acquired deficiency of Klotho might contribute to DGF‐associated chronic allograft dysfunction. Abstract : The authors demonstrate a direct involvement of complement in regulating the expression of anti‐aging factor Klotho in a swine model of ischemia/reperfusion injury, and lower levels of renal and soluble Klotho in patients affected by delayed graft function years after transplantation.